Development of targeted, theory-informed interventions to improve bronchiolitis management - Libby Haskell; Emma J. Tavender; Catherine L. Wilson; Sharon O'Brien; Franz E. Babl; Meredith L. Borland; Elizabeth Cotterell; Nicolette Sheridan; Ed Oakley; Stuart R. Dalziel; on behalf of the Paediatric Research in Emergency Departments International Collaborative (PREDICT) (BMC, 2021)
Abstract Background Despite international guidelines providing evidence-based recommendations on appropriate management of infants with bronchiolitis, wide variation in practice occurs. This results in infants receiving care of no benefit, with associated cost and is potentially harmful. Theoretical frameworks are increasingly used to develop interventions, utilising behaviour change techniques specifically chosen to target factors contributing to practice variation, with de-implementation often viewed as harder than implementing. This paper describes the stepped process using the Theoretical Domains Framework (TDF) to develop targeted, theory-informed interventions which subsequently successfully improved management of infants with bronchiolitis by de-implementing ineffective therapies. Explicit description of the process and rationale used in developing de-implementation interventions is critical to dissemination of these practices into real world clinical practice. Methods A stepped approach was used: (1) Identify evidence-based recommendations and practice variation as targets for change, (2) Identify factors influencing practice change (barriers and enablers) to be addressed, and (3) Identification and development of interventions (behaviour change techniques and methods of delivery) addressing influencing factors, considering evidence of effectiveness, feasibility, local relevance and acceptability. The mode of delivery for the intervention components was informed by evidence from implementation science systematic reviews, and setting specific feasibility and practicality. Results Five robust evidence-based management recommendations, targeting the main variation in bronchiolitis management were identified: namely, no use of chest x-ray, salbutamol, glucocorticoids, antibiotics, and adrenaline. Interventions developed to target recommendations addressed seven TDF domains (identified following qualitative clinician interviews (n = 20)) with 23 behaviour change techniques chosen to address these domains. Final interventions included: (1) Local stakeholder meetings, (2) Identification of medical and nursing clinical leads, (3) Train-the-trainer workshop for all clinical leads, (4) Local educational materials for delivery by clinical leads, (5) Provision of tools and materials targeting influencing factors, and prompting recommended behaviours, and (6) Audit and feedback. Conclusion A stepped approach based on theory, evidence and issues of feasibility, local relevance and acceptability, was successfully used to develop interventions to improve management of infants with bronchiolitis. The rationale and content of interventions has been explicitly described allowing others to de-implement unnecessary bronchiolitis management, thereby improving care.